Evaluation of the Efficacy and Safety of Atropine Eye Drops 0.01% in Slowing Myopia Progression in Children and Adolescents with High and Low Myopia: A Quasi experimental study - Masud, Hannan; Batool, Fizzah; Nasir, Samra; Hannan, Sarah (Pakistan Armed Forces Medical Journal, 2025)
Objective: To evaluate the efficacy and safety of Atropine eye drops 0.01% in slowing myopia progression in children and adolescents with high and low myopia. Study Design: Quasi experimental study. Place and Duration of Study: Combined Military Hospital, Kharian Pakistan, from Sep 2021 to Jul 2024 Methodology: Seventy-two patients (144 eyes) aged 5-18 years (8.47±3.04 years) with myopia progression (≥0.25mm AL or ≥0.75D SE over 3 months). Participants were stratified by high myopia (HM, AL>26.5mm, SE> -6D) and low myopia (LM, AL<26.5mm, SE< -6D) and randomly assigned to Atropine 0.01% or Control Groups. Double-blinding ensured neither participants nor investigators were aware of Group assignment. Both Groups received treatment for 24 months, with quarterly follow-ups recording AL and SE. The Control Group received placebo eye drops, identical in appearance and administration to the Atropine eye drops. Primary outcome measures included changes in AL and SE from baseline to 24 months, while secondary outcome measures included adverse events and quality of life questionnaires. Results: In this study, total 144 eyes of 72 patients were included, with 72 eyes in intervention Group (Atropine eye drops 0.01%) and 72 eyes in Control Group (placebo eye drops). Atropine 0.01% eye drops significantly reduced myopia progression in children, with the Atropine Group showing smaller increases in axial length (25.32±1.53 mm vs. 25.80±1.77 mm) and spherical equivalent .... Conclusion: The 0.01% Atropine eye drops effectively slowed myopia progression in both HM and LM Groups, with similar efficacy across different severity ranges.